Ultraviolet-Absorption Spectra of Dry Bacterial Spores - Bailey, Glen F. (1965)
Bailey, Glen F. (Western Regional Research Laboratory, Albany, Calif.), Saima Karp, and L. E. Sacks. Ultraviolet-absorption spectra of dry bacterial spores. J. Bacteriol. 89:984–987. 1965.—The possibility of obtaining reasonably satisfactory ultraviolet-absorption spectra of dry spores embedded in KBr has been demonstrated. Such spectra show the three peaks characteristic of calcium dipicolinate. The dipicolinate spectra are more distinct when reference pellets containing appropriate amounts of the analogous spore coats are employed. These spectra are considered evidence that some type of calcium-dipicolinic acid chelate accounts for at least part of the calcium and dipicolinic acid content of the spore.